Long-Term Lithium Therapy: Side Effects and Interactions - Ewa Ferensztajn-Rochowiak; Janusz K. Rybakowski (MDPI AG, 2023)
Lithium remains the drug of first choice for prophylactic treatment of bipolar disorder, preventing the recurrences of manic and depressive episodes. The longitudinal experiences with lithium administration greatly exceed those with other mood stabilizers. Among the adverse side effects of lithium, renal, gastrointestinal, neurological, thyroid, metabolic, cognitive, dermatological, cardiologic, and sexual are listed. Probably, the most important negative effect of lithium, occurring mostly after 10-20 years of its administration, is interstitial nephropathy. Beneficial side-effects of long-term lithium therapy also occur such as anti-suicidal, antiviral, and anti-dementia ones. Pharmacokinetic and pharmacodynamic interactions of lithium, mostly those with other drugs, may have an impact on the success of long-term lithium treatment. This paper makes the narrative updated review of lithium-induced side-effects and interactions that may influence its prophylactic effect in bipolar disorder. Their description, mechanisms, and management strategies are provided. The papers appearing in recent years focused mainly on the long-term lithium treatment are reviewed in detail, including recent research performed at Department of Psychiatry, Poznan University of Medical Sciences, Poland. Their own observations on ultra-long lithium treatment of patients with bipolar disorder are also presented. The review can help psychiatrists to perform a successful lithium prophylaxis in bipolar patients.